Indeks słów zakazanych – emigracja - Rudnicki, Bogdan (Załącznik Kulturoznawczy, 2024)
This article is a modified version of the speech delivered during the “Marek Hłasko Today” Conference. Its basis are fragments of the chapter Crossroads in the book Hłasko – Our Non-Contemporary (published by Universitas Cracow 2024). It describes Hłasko’s likely motivations, which in connection with the witch hunt against him in the Communistruled Poland, caused the writer to emigrate in 1958. His emigration was of particular significance because of the idol status Hłasko possessed, which he had attained not only in the eyes of the young generation. That is why, among other things, a long and brutal campaign to discredit him was launched, on top of the total “censorship ban on mentioning his name” and prohibition of publication of any of his works.